2009
DOI: 10.1029/2009gl038068
|View full text |Cite
|
Sign up to set email alerts
|

Does sedimentary 231Pa/230Th from the Bermuda Rise monitor past Atlantic Meridional Overturning Circulation?

Abstract: Ocean circulation may have undergone reductions and reinvigorations in the past closely tied to regional climate changes. Measurements of 231Pa/230Th ratios in a sediment core from the Bermuda Rise have been interpreted as evidence that the Atlantic Meridional Overturning Circulation (AMOC) was weakened or completely eliminated during a period of catastrophic iceberg discharges (Heinrich‐Event 1, H1). Here we present new data from the Bermuda Rise that show further 231Pa/230Th peaks during Heinrich‐2 (H2) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
144
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(161 citation statements)
references
References 27 publications
(41 reference statements)
13
144
0
4
Order By: Relevance
“…Data north of 45°S were used for the LGM and HS1 to account for the northward shift of the Southern Ocean opal belt during the LGM, in keeping with Yu et al 1 The average 231 Pa/ 230 Th ratio in LGM sediments (0.065±0.005; n ¼ 79) is similar to the value obtained by Yu et al 1 (0.059±0.007; n ¼ 26; Fig. 2); this study 15,16,[20][21][22][23]25,27,28,30,39,40,[54][55][56] . The average ratio for HS1 (0.074 ± 0.009; n ¼ 26) is somewhat greater than the LGM value, but not significantly different at the 95% confidence level; this study 15,16,21,22,25,27,30,39,40,54 .…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Data north of 45°S were used for the LGM and HS1 to account for the northward shift of the Southern Ocean opal belt during the LGM, in keeping with Yu et al 1 The average 231 Pa/ 230 Th ratio in LGM sediments (0.065±0.005; n ¼ 79) is similar to the value obtained by Yu et al 1 (0.059±0.007; n ¼ 26; Fig. 2); this study 15,16,[20][21][22][23]25,27,28,30,39,40,[54][55][56] . The average ratio for HS1 (0.074 ± 0.009; n ¼ 26) is somewhat greater than the LGM value, but not significantly different at the 95% confidence level; this study 15,16,21,22,25,27,30,39,40,54 .…”
Section: Discussionsupporting
confidence: 80%
“…Previous studies have documented a strong relationship between sedimentary composition, specifically opal content, and the 231 Pa/ 230 Th ratio in both sediment traps 17 and downcore records [22][23][24] . Some authors have sought to minimize the effects of scavenging by excluding diatom-rich intervals 25 or high-flux sites, where 231 Pa/ 230 Th and opal flux correlate the most strongly 20 .…”
Section: Spatiomentioning
confidence: 94%
“…McManus et al (2004) suggested a near total collapse of Atlantic MOC during Heinrich event 1 based on a sedimentary Pa/Th record from the Bermuda Rise. However, since the adsorbed sedimentary Pa/Th signal is also highly sensitive to particle compositions (biogenic silica content) such an interpretation has to be treated with caution and Atlantic MOC reduction may not have been so severe (Chase et al, 2002;Hall et al, 2006;Keigwin and Boyle, 2008;Gherardi et al, 2009;Lippold et al, 2009). In addition, several of the major Heinrich IRD discharge events (H1, H2, H4) were apparently accompanied by meltwater precursor events originating from the Northwest European Ice Sheet (NWEIS) suggesting that ice sheet collapse of European origin may have pre-conditioned the MOC in the North Atlantic (Peck et al, 2007b).…”
Section: Climate and Hydrographymentioning
confidence: 99%
“…The application of the above principle to interpret sediment 231 Pa / 230 Th as the strength of Atlantic meridional overturning circulation (AMOC), however, can be complicated by other factors, leading to uncertainties in using 231 Pa / 230 Th as a proxy for past circulation (Keigwin and Boyle, 2008;Lippold et al, 2009;Scholten et al, 2008). In addition to the ocean transport, sediment 231 Pa / 230 Th is also influenced by particle flux and composition (Chase et al, 2002;Geibert and Usbeck, 2004;Scholten et al, 2008;4724 S. Gu and Z. Liu: 231 Pa and 230 Th in the ocean model of the Community Earth System Model (CESM1.3) Siddall et al, 2007;Walter et al, 1997).…”
Section: Introductionmentioning
confidence: 99%